Resveratrol ameliorates liver fibrosis induced by nonpathogenic Staphylococcus in BALB/c mice through inhibiting its growth - Zhiqin Li; Jianxia Dong; Meng Wang; Jingya Yan; Yushu Hu; Yang Liu; Yajie Pan; Hua Li (BMC, 2022)
Abstract Background The altered gut microbiota is implicated in the pathogenesis of liver fibrosis. Resveratrol is a candidate for the treatment of liver fibrosis, which could ameliorate the dysregulation of gut microbiota in mice. This study aimed to clarify the role and mechanism of resveratrol in gut microbiota during liver fibrosis. Methods A mouse model of liver fibrosis induced by CCl4 was conducted to assess the effect of resveratrol on liver fibrosis. The changes of gut microbiota in liver fibrotic mice after resveratrol intervention were assessed using 16S ribosomal RNA sequencing. The mechanism of the gut microbiota dysregulation in liver fibrosis was investigated by Sirius red staining, immunohistochemical assay, bacterial translocation (BT), EUB338 fluorescence in situ hybridization, immunofluorescence, trans-epithelial electrical resistance analysis and paracellular permeability analysis. Results Resveratrol relieved CCl4-induced liver fibrosis. Besides, resveratrol restrained the gut microbiota Staphylococcus_lentus and Staphylococcus_xylosus in the liver fibrotic mice, and the Staphylococcus_xylosus and Staphylococcus_lentus facilitated the occurrence of BT and the cultures of them enhanced the permeability of intestine. The in vivo assay corroborated that the excessive Staphylococcus_xylosus and Staphylococcus_lentus canceled the protecting effect of resveratrol on liver fibrosis, and Staphylococcus_xylosus or Staphylococcus_lentus alone had a limited impact on the liver injury of normal mice. Conclusion Resveratrol ameliorated liver fibrosis by restraining the growth of Staphylococcus_xylosus and Staphylococcus_lentus.